2021
DOI: 10.1016/j.jcot.2020.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and effectiveness of eccentric vs. concentric muscle strengthening in rotator cuff partial tears and moderate to severe shoulder pain. A randomized pilot study

Abstract: Introduction: Rotator cuff tears are the main cause of shoulder pain and disability. First line of treatment is conservative; there is evidence regarding the advantage of using eccentric over concentric exercises in tendinopathies, but there are no evidence-based recommendations on starting strengthening exercise during painful phases nor on the effectiveness and advantages of eccentric vs. concentric exercise in rotator cuff tears. Objective: To evaluate the tolerance of a resistance strengthening program and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…11,19 Concurrently, numerous studies have shown that eccentric training is effective in preventing muscle sprains, recovering from muscle atrophy, and treating tendon pain. 34,41 Our study demonstrated that exercise stimulation with different muscle contraction patterns can initially regulate macrophages according to the magnitude of the inflammatory response at the injury site, resulting in different states of fibroblast proliferation, cytoplasmic matrix deposition, and growth factor concentration, and demonstrating the benefits of eccentric muscle contraction.…”
Section: Discussionmentioning
confidence: 68%
“…11,19 Concurrently, numerous studies have shown that eccentric training is effective in preventing muscle sprains, recovering from muscle atrophy, and treating tendon pain. 34,41 Our study demonstrated that exercise stimulation with different muscle contraction patterns can initially regulate macrophages according to the magnitude of the inflammatory response at the injury site, resulting in different states of fibroblast proliferation, cytoplasmic matrix deposition, and growth factor concentration, and demonstrating the benefits of eccentric muscle contraction.…”
Section: Discussionmentioning
confidence: 68%
“…Regarding the Level of Evidence, 5 studies were level I RCTs 30,31,34,37,38 ; 5 level III PCC studies 7,8,32,33,42 ; and 1 level IV prospective case-series study 36 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the Level of Evidence, 5 studies were level I RCTs 30,31,34,37,38 ; 5 level III PCC studies 7,8,32,33,42 ; and 1 level IV prospective case-series study. 36 The 11 studies reviewed included a total of 454 patients, with a minimum follow-up of 3 months.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Macías-Hernández y colaboradores publicaron un artículo en el que compararon un programa de rehabilitación que incluyó, termoterapia, ejercicios de movilidad, estiramiento y fortalecimiento excéntrico versus concéntrico en pacientes con lesiones parciales de MR en fases dolorosas, donde mostraron una adecuada tolerancia del fortalecimiento, mejoría en el dolor y la funcionalidad en ambos grupos, sin diferencias significativas entre ellos. 45 De forma general se recomienda comenzar con un tratamiento conservador de 12 semanas, para poder evaluar adecuadamente el resultado. Los protocolos publicados son heterogéneos, pero generalmente se progresan de forma mensual.…”
Section: Rehabilitaciónunclassified